2012
DOI: 10.1111/j.1574-6976.2012.00335.x
|View full text |Cite
|
Sign up to set email alerts
|

HIV latency: experimental systems and molecular models

Abstract: Current antiretroviral therapy for HIV-1 infection effectively suppresses but does not eradicate HIV-1. Patients on Highly Active Anti-Retroviral Therapy (HAART) maintain a persistent low-level viremia requiring lifelong adherence to antiretroviral therapies. This viremia may arise from latently infected reservoirs such as resting memory CD4+ T-cells or sanctuary sites where drug penetration is suboptimal. Understanding the mechanisms of HIV latency will help efforts to eradicate the infection. This review exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 54 publications
1
71
0
Order By: Relevance
“…SWI/SNF complexes control the nucleosome landscape at active promoters and are required for HIV Tat transactivation [29]. Interestingly, we found that two core components of the SWI/SNF ATP-dependent BAF chromatin remodeling complex, SWI/SNF related, matrix associated, Actin dependent Regulator of Chromatin, subfamily D1 (SMARCD1), member 1 BAF60, and SMARCB1 (SNF5/INI1) were down-regulated two hours following vorinostat (red arrowhead Figure 6B ).…”
Section: Resultsmentioning
confidence: 92%
“…SWI/SNF complexes control the nucleosome landscape at active promoters and are required for HIV Tat transactivation [29]. Interestingly, we found that two core components of the SWI/SNF ATP-dependent BAF chromatin remodeling complex, SWI/SNF related, matrix associated, Actin dependent Regulator of Chromatin, subfamily D1 (SMARCD1), member 1 BAF60, and SMARCB1 (SNF5/INI1) were down-regulated two hours following vorinostat (red arrowhead Figure 6B ).…”
Section: Resultsmentioning
confidence: 92%
“…As such cells are not immortalized or clonal, primary cell models might offer a more physiologically relevant representation of latency than cell lines, and their responsiveness to stimuli might be more representative of in vivo biology. Several cell models are currently being used 8188 (reviewed in REFS 89,90), and there are important differences in the cell subsets, viral strains and mechanisms that are used to establish latency 89,90 (TABLE 1). A careful comparison of latent HIV-1 reactivation by different stimuli across multiple primary cell models revealed diverse responses to the same stimuli.…”
Section: Model Systems Of Hiv-1 Latencymentioning
confidence: 99%
“…Despite these challenges, several in vitro latency models exist, which have led to important observations about how latently infected cells are maintained and reactivated (reviewed in references [16, 17]).…”
Section: Introductionmentioning
confidence: 99%